2021
DOI: 10.1186/s13578-021-00664-8
|View full text |Cite
|
Sign up to set email alerts
|

Persistent deficiency of mucosa-associated invariant T (MAIT) cells during alcohol-related liver disease

Abstract: Background Alcohol-related liver disease (ALD) is a major cause of chronic liver diseases. Inflammatory response is a basic pathological feature of ALD. Mucosal-associated invariant T(MAIT) cells are a novel population of innate immune cells, which may be depleted in various inflammatory diseases. However, the changes of MAIT cell in ALD remains unclear. Results In this study, the levels of MAIT cell were significantly decreased in patients with al… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…It follows that organ systems which rely on immune signaling for proper functioning are also impaired. Some systems, like the nervous system may be altered in subtle ways that alter behavior ( 75 ). In contrast, systems which directly encounter pathogens from the environment can become more susceptible to infection and injury ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“…It follows that organ systems which rely on immune signaling for proper functioning are also impaired. Some systems, like the nervous system may be altered in subtle ways that alter behavior ( 75 ). In contrast, systems which directly encounter pathogens from the environment can become more susceptible to infection and injury ( 76 , 77 ).…”
Section: Discussionmentioning
confidence: 99%
“… 88 Previously, Riva et al 89 reported that peripheral blood MAIT cell frequency was significantly lower in patients with ALD (alcohol-related cirrhosis and severe alcoholic hepatitis) than in healthy volunteers, especially in patients with severe alcoholic hepatitis, where the decrease was most obvious. According to Zhang et al, 90 the combined effects of IL-12, IL-18, and IL-8 could be responsible for the decrease in MAIT cells in patients with ALD. Compared with control subjects, peripheral blood MAIT cells expressed higher levels of CD69 and HLA-DR, but produced significantly less IL-17, granzyme B, and CD107a.…”
Section: Mucosal-associated Invariant T Cells In Hepatobiliary Diseasesmentioning
confidence: 97%
“…As mentioned above, our group recently identified a novel population of human FoxP3 + T2NKT cells that might exert immunoregulatory functions in this scenario ( 40 ). Alcoholic-related cirrhosis and severe alcoholic hepatitis patients had a dramatic depletion and hyperactivated circulating MAIT cells ( 127 , 128 ). Dysfunctional MAIT cells could explain the susceptibility to infection of these patients ( 127 , 128 ).…”
Section: Alcohol-induced Hepatitis and Drugsmentioning
confidence: 99%